2017
DOI: 10.1002/for.2464
|View full text |Cite
|
Sign up to set email alerts
|

Understanding algorithm aversion: When is advice from automation discounted?

Abstract: Forecasting advice from human advisors is often utilized more than advice from automation. There is little understanding of why “algorithm aversion” occurs, or specific conditions that may exaggerate it. This paper first reviews literature from two fields—interpersonal advice and human–automation trust—that can inform our understanding of the underlying causes of the phenomenon. Then, an experiment is conducted to search for these underlying causes. We do not replicate the finding that human advice is generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 49 publications
9
124
0
Order By: Relevance
“…Reconciling this body of research is surely important, yet existing work only provides speculative explanations. For instance, Prahl and Van Swol () suggest that their experiment included performance feedback and consistent message characteristics (i.e., only the source description was varied), whereas the set up in Önkal et al () did not include performance feedback and manipulated message characteristics across source types. Understanding how these factors interact with economic incentivization is an empirical question that deserves attention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reconciling this body of research is surely important, yet existing work only provides speculative explanations. For instance, Prahl and Van Swol () suggest that their experiment included performance feedback and consistent message characteristics (i.e., only the source description was varied), whereas the set up in Önkal et al () did not include performance feedback and manipulated message characteristics across source types. Understanding how these factors interact with economic incentivization is an empirical question that deserves attention.…”
Section: Resultsmentioning
confidence: 99%
“…What manifests from these pre-existing expectations is a paradigm in which human decision makers perceive and respond to advice generated by algorithms differently than advice generated by humans, even if the advice itself is identical. Various mechanisms underlying this difference in response are demonstrated throughout the literature, such as the tendency for humans to seek a social or parasocial relationship with the source of advice (Alexander, Blinder, & Zak, 2018;Önkal, Goodwin, Thomson, Gonul, & Pollock, 2009;Prahl & Van Swol, 2017), the persistent belief that human error is random and repairable whereas algorithmic error is systematic (Dietvorst et al, 2015;Dietvorst, Simmons, & Massey, 2016;Highhouse, 2008b), experts' domain confidence leading to underutilization of seemingly unnecessary algorithmic aids (Arkes, Dawes, & Christensen, 1986;Ashton, Ashton, & Davis, 1994), or a lack of training preventing a human user from properly utilizing an algorithmic aid (Mackay & Elam, 1992; cf. Green & Hughes, 1986).…”
Section: Problem: False Expectationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietvorst et al (2016) found that the algorithm aversion could be eased by ceding a small amount of control. Prahl and Van Swol (2017) theorise the phenomenon in the psyhocological framework. Fehr et al (2013), Bartling et al (2014), and Owens et al (2014) theorize the value of authority and control in the principal-agent framework.…”
Section: Related Literaturementioning
confidence: 99%